Development of a Guide to Preparation of Mathematics Questions Based on Higher Order Thinking Skills and Strengthening Character Education for Middle School Teachers - Ibrahim, Ibrahim; Kuswidi, Iwan; Arfinanti, Nurul (Program Studi Matematika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2020)
The objectives of public devotion based on nationally excelled research this covers: (1) to develop a mathematical problem composing guide based on HOTS and SCE for qualified Madrasah Tsanawiyah teachers, (2) to provide training a mathematical problem composing based on HOTS and SCE for qualified Madrasah Tsanawiyah teachers using the developed guide. This study uses a 4-D (Four D) development research design model according to Thiagarajan, et al (1974: 5). This research model includes 4 main stages, namely the defining stage, followed by the design stage, then towards the development stage, and finally the distribution phase. The research instruments included: (a) the scale of the assessment of the quality of mathematical composing guide based on HOTS and SCE for Madrasah Tsanawiyah teachers, (b) scale of appraisal user response for guidebook, and (c) the Pre Test and Post Test Problem Sheets. The results of the study concluded that the guidebook for mathematical problem composing for SMP / MTs based on HOTS and SCE met the specified quality criteria, which were at least in the good category. In this study, the developed guidebook obtained an evaluation in the excellent category. However, testing to determine the level of practicality has not been done.